The Relevance of Establishing a Halal Study Center at State Islamic University - Syalawaty, Diyan; Rifli, Dandy Firmansyah; Saputra, Andryan; Utami, Wiji; Tanti, Tanti; Deliza, Deliza; Syafitri, Rita; Widiyanto, Widiyanto (Journal of Quality Assurance in Islamic Education (JQAIE), 2021)
This study aims to explore the Halal Study Center in every State Islamic University in Indonesia. Data collection in this study was gained using the interview method and also literature review. Interviews were conducted directly with several sources, while the literature review was performed by collecting journals regarding the research problems. The findings show that eight State Islamic University already have halal study centers out of the total number of State Islamic University in Indonesia, 27 in total. Furthermore, some of the State Islamic University that have established halal study centers also have development activities. The practical implications of this paper provide new knowledge for the State Islamic University that will establish a halal study center. This is the first article that discusses the development of research trends in the halal study center at the State Islamic University and provides the latest comprehensive literature review until 2021.